2010
DOI: 10.1177/193229681000400223
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Mechanism of Action and Clinical Efficacy of Recombinant Human Hyaluronidase Coadministration with Current Prandial Insulin Formulations

Abstract: Abbreviations: (A1C) derived average glucose, (C max ) peak plasma concentration, (PK) pharmacokinetics, (PPG) postprandial plasma glucose, (rHuPH20) recombinant human hyaluronidase, (SC) subcutaneous, (t max ) time to peak plasma concentration Keywords: diabetes, glycemic control, hyaluronidase, rHuPH20, ultrafast insulin AbstractFor patients with type 1 or type 2 diabetes, achieving good glycemic control is critical for successful treatment outcomes. As many patients remain unable to reach glycemic goals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 37 publications
(81 reference statements)
2
33
0
Order By: Relevance
“…A second study in healthy subjects also reported a lower intra-subject variability with rHuPH20 coadministration (94). A phase 2 standardized meal-test study in patients with type 1 diabetes examined whether the accelerated insulin absorption has favorable consequences on the control of postprandial glycemic excursions (94). As in the phase 1 studies, the coadministration of rHuPH20 with regular insulin or lispro yielded an accelerated insulin concentration profile that was accompanied by a significant reduction in both mean peak and total post-meal glucose concentrations compared to either insulin alone.…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 96%
See 4 more Smart Citations
“…A second study in healthy subjects also reported a lower intra-subject variability with rHuPH20 coadministration (94). A phase 2 standardized meal-test study in patients with type 1 diabetes examined whether the accelerated insulin absorption has favorable consequences on the control of postprandial glycemic excursions (94). As in the phase 1 studies, the coadministration of rHuPH20 with regular insulin or lispro yielded an accelerated insulin concentration profile that was accompanied by a significant reduction in both mean peak and total post-meal glucose concentrations compared to either insulin alone.…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 96%
“…As in the phase 1 studies, the coadministration of rHuPH20 with regular insulin or lispro yielded an accelerated insulin concentration profile that was accompanied by a significant reduction in both mean peak and total post-meal glucose concentrations compared to either insulin alone. Post-meal hypoglycemia was reported to be generally mild and the overall hypoglycemic risk comparable for lispro with or without rHuPH20 and reduced for regular insulin with rHuPH20 compared with regular insulin alone (94). Clinical studies reported a good tolerability profile without severe adverse effects, but there is no safety data so far regarding the repeated or long term exposure to recombinant hyaluronidase.…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 99%
See 3 more Smart Citations